CROSSING STROKES EXAMINATION FROM CROMATICITY DIAGRAM - Roshan Giri; Shanker Prasad Chimouriya; Bal Ram Ghimire (Science Heritage Journal)
It is aimed to find exact chronological order in crossing strokes with the help of chromaticity diagram in this experiment. Since, surface on point of intersection corresponds to second stroke in crossing two lines, it is assumed that chromaticity co-ordinate (x,y) of the crossing stroke should be similar to that of second stroke rather than first stroke. We carried out this experiment on crossing strokes made from differernt writing pens and printers. We did experiment many times by preparing different samples each time in both homogeneous and heterogeneous crossing strokes but we get positive and conclusive results only in most of heterogeneous crossing strokes. This work is very helpful to questioned document examiners to examine forgery in document.